The drawing of the Mark of Cain : a socio-historical analysis of the growth of anti-Jewish stereotypes - Arkel, D. van (Online access: OAPEN Open Research Library (ORL), 2009)
Anti-Semitism is an extraordinary historical phenomenon. Over some two thousand years it has manifested itself in different guises, from mild to genocidal in different places and at different times. Under what conditions do anti-Semitic movements emerge? What evokes large-scale stereotyping? What does it take for people to act upon these stereotypes? And in what way does anti-Semitism differ from other forms of racism?